2008
DOI: 10.1016/j.exphem.2008.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Mouse fetal and embryonic liver cells differentiate human umbilical cord blood progenitors into CD56-negative natural killer cell precursors in the absence of interleukin-15

Abstract: Objective-Human NK cell maturation involves the orderly acquisition of NK cell receptors. Our aim was to understand how stromal interactions and cytokines are important in this developmental process.Methods-Human UCB CD34 + /Lin − /CD38 − cells were cultured on two murine stromal cell lines (AFT024 and EL08-1D2) in a switch culture to study NK cell development.Results-When human progenitors were cultured on AFT024 with IL-3 and Flt3-L in the absence of IL-15, NK cell differentiation occurred, albeit at low fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 54 publications
0
39
0
Order By: Relevance
“…IL-15 has been considered to have a more physiologic role than IL-2 in NK development (30). Notably, IL-15-independent NK cell differentiation has recently been published (6). This culture system, however, has been reported to be stromal cell dependent while the potential molecules and signaling pathways are unknown and, thus, the conclusion whether IL-15 is indispensable is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-15 has been considered to have a more physiologic role than IL-2 in NK development (30). Notably, IL-15-independent NK cell differentiation has recently been published (6). This culture system, however, has been reported to be stromal cell dependent while the potential molecules and signaling pathways are unknown and, thus, the conclusion whether IL-15 is indispensable is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, IL-15 is considered to be required for in vitro NK cell development and virtually most current protocols for human NK cell differentiation culture depend on IL-15. IL-15-independent NK cell differentiation has been reported in which human cord blood (CB) 9 cells are cocultured with murine stromal cell lines (6). Signaling, however, substituting IL-15 signaling that is responsible for the NK cell differentiation in this culture system was not described.…”
mentioning
confidence: 99%
“…Their results show that NK cell receptor fate is acquired after NK cell commitment and does not require stromal presentation of MHC-1 by the stromal cells. 87 Later in 2008, McCullar et al 88 investigated AFT024 and EL08-1D2 potential to generate NK cells, and found that EL08-1D2 is significantly better at recapitulating NK cell development. EL08-1D2 was cloned from embryonic liver at day 11, and was proven in this study to support the generation of NK cells from human hematopoietic precursors, and used also by other groups.…”
Section: Generation Of Natural Killer Cells From Hscs M Luevano Et Almentioning
confidence: 99%
“…1 cells cocultured with stroma and recombinant cytokines can differentiate into both cNK cells and ILC22 cells, 7,19,20,22 but the lineage relationship between these two cell types in humans has been debated. 10,15,23,24 To investigate this, CD34 1 cells were cultured with IL-3 (for the first week), SCF, FLT3L, IL-7, and IL-15 for 3 weeks.…”
Section: Human Cd34mentioning
confidence: 99%